"Incident Teaching (IT)" Lecture Series – Incorporating Education Surrounding Clinical Incidents and Complaints into Foundation Year 1 (FY1) Doctors' Induction. Issue 1 (1st January 2021) - Manalayil, Jyothis; Kouranloo, K; Horne, L
ABSTRACT: Patient safety incidents are any unintended or unexpected incidents which potentially could, or did, lead to harm to patients. Incident reports are crucial to improve patients' care and to identify further actions needed to prevent harm. A common view among the FY1 doctors in our local NHS Trust involved a fearful opinion surrounding being involved in clinical incidents. Significant anxiety in those situations prompted the need for a focus on the topic of "clinical incidents" during their induction to the Trust in two consecutive years of 2018 and 2019. A near-peer lecture series was delivered to new FY1 with qualitative pre- and post-lecture series feedbacks. Results from lecture series from two consecutive years showed all FY1 doctors agreed or strongly agreed that they had a good understanding of incidents following the lecture. Compared with their pre-course feedback, there was an increase of 6-fold (2018) and 8-fold (2019) in those that strongly agreed. Post-course, more than 90% of doctors reported that they would feel comfortable sharing with colleagues their involvement in an incident. In a growing culture of blame and litigation, it is important to address the harm associated with a blame-based culture. The process of investigating an incident has the potential to expose the areas of deficiency relating to an individual. Reducing stigma associated with incidents could theoretically reduce the second victim phenomenon. An open culture to incident reporting is a fundamental part of medical education and quality improvement. Encouraging this attitude amongst medical professionals and creating a supporting environment surrounding sharing of experiences will help to form a generation of doctors that see incident reporting in a positive light. Our model of lecture series could be utilised in other UK Foundation Programmes with the aim of enriching the FY1s' induction period.